2013
DOI: 10.1007/s10143-013-0487-5
|View full text |Cite
|
Sign up to set email alerts
|

Emergency EC-IC bypass for symptomatic atherosclerotic ischemic stroke

Abstract: Previous studies have shown that extracranial-intracranial (EC-IC) bypass surgery has no preventive effect on subsequent ipsilateral ischemic stroke in patients with symptomatic atherosclerotic internal carotid occlusion and hemodynamic cerebral ischemia. A few studies have assessed whether an urgent EC-IC bypass surgery is an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 11 publications
1
30
0
2
Order By: Relevance
“…A small case series recently reported that urgent STA-MCA bypass stabilized the progression of ischemia and/or reversed the symptoms in majority of the cases. In addition, there were no surgical complications or hemorrhage 9,18,23) . Thus, it may be possible to prevent an ongoing ischemic event thereby stopping and/ or reversing neurological symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…A small case series recently reported that urgent STA-MCA bypass stabilized the progression of ischemia and/or reversed the symptoms in majority of the cases. In addition, there were no surgical complications or hemorrhage 9,18,23) . Thus, it may be possible to prevent an ongoing ischemic event thereby stopping and/ or reversing neurological symptoms.…”
Section: Discussionmentioning
confidence: 88%
“…Only few descriptive case series exist describing the role of urgent EC-IC bypass in treating patients with acute and progressive ischemic symptoms despite optimal medical therapy because of acute atherosclerotic stenoocclusive event; these report good results in term of patients' outcome. 50,54,55 These case series all have a retrospective design and are therefore vulnerable to selection bias. Furthermore, they have been published before the recent RCTs reinforcing the role of endovascular therapy for stroke.…”
Section: Considerations In Patients With Atherosclerotic Steno-occlusmentioning
confidence: 99%
“…We however hypothesize that there is a small number of patients having acute stroke with persistent penumbra that cannot benefit from other acute revascularization interventions and may benefit from emergent EC-IC bypass, if the procedure can be performed with low enough morbidity. 55 One of the key elements is to define the method to select these patients having acute stroke and who have persistent ischemic penumbra with limited core infarct, indicating ischemic tissue still viable and salvageable if local perfusion is efficiently restored. 54 The concept of 'mismatch' is an attempt to define ischemic penumbra by neuroimaging 49,53 A detailed analysis and definition of the mismatch concept is beyond the scope of this review, and we refer to the relative literature.…”
Section: Strokementioning
confidence: 99%
See 2 more Smart Citations